PENGARUH STRATEGI PROMOSI DAN KUALITAS PRODUK PADA NIAT BELI BERULANG DI SHOPEE (Studi Kasus Kabupaten Grobogan) - Yuli Alfiana; Sulartopo Sulartopo; Siti Kholifah (EKOBIS, 2026)
Shopee is one of the dominant platforms in Indonesia because of the rapid growth of e-commerce. However, consumer loyalty is not only determined by the first shopping experience but also by the intention of repeat purchase. Repeat purchase intention is mostly affected by promotion strategy and product quality. This research used quantitative approach with multiple linear regression analysis processed using SPSS. The data were collected by using online questionnaire to 100 respondents who were active Shopee users in Grobogan Regency. The research instrument was tested for validity , reliability , and classical assumption test (normality, multicollinearity, heteroscedasticity). The results of the study indicate that the promotional strategy has a positive and significant effect on the repeated purchase intention. product quality also positively and significantly affect repurchase intention. Together these variables contribute largely to the increase of intention to repeat purchases of Shopee consumers in Grobogan Regency.